2017
DOI: 10.1534/genetics.117.300262
|View full text |Cite|
|
Sign up to set email alerts
|

Cell Biology of the Mitochondrion

Abstract: In the article by A. M. van der Bliek, M. M. Sedensky, and P. G. Morgan entitled "Cell Biology of the Mitochondrion" on page 855, the second full paragraph incorrectly attributed the development of a luciferase-expressing strain in Caenorhabditis elegans to the Meyer laboratory. The sentence beginning "Perhaps most importantly. . ." was deleted and replaced with the following sentences:"In the Glover and Pettitt laboratories, Lagido et al. (2008) developed a luciferase-expressing strain that allowed in vivo a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
231
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 311 publications
(238 citation statements)
references
References 230 publications
(319 reference statements)
1
231
0
6
Order By: Relevance
“…Previous C. elegans RNAi screens have shown that many mitochondrial gene inactivations are lethal (Rea et al, 2007). However, viable reduction-of-function mutants have been characterized (van der Bliek et al, 2017). We tested a viable spg-7(ad2249) mutant (Zubovych et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous C. elegans RNAi screens have shown that many mitochondrial gene inactivations are lethal (Rea et al, 2007). However, viable reduction-of-function mutants have been characterized (van der Bliek et al, 2017). We tested a viable spg-7(ad2249) mutant (Zubovych et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…C. elegans nduf-7(et19), isp-1(qm150), and clk-1(qm30) mutant animals grown on the E. coli Δfes::kan mutant also dramatically arrest as L1 larvae (Table 3; Figure S5) while particular other C. elegans mitochondrial mutants including gas-1(fc21), nduf-2.2(ok2397), nuo-6(qm200), mev-1(kn1), and ucr-2.3(pk732) did not arrest when grown on the E. coli Δfes::kan mutant (Table 3; Figure S5). nduf-7(et19) is a partial loss-offunction mutation in nduf-7 (NADH-ubiquinone oxidoreductase Fe-S), a subunit of the mitochondrial electron transport chain complex I (Rauthan et al, 2015;van der Bliek et al, 2017). nduf-7(et19) mutant animals strongly activate UPR mt , have a reduced respiration rate and longer lifespan (Rauthan et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mitochondrial fission is mediated by the dynaminrelated protein DRP1. DRP1 is recruited to the outer mitochondrial membrane via its receptor proteins, such as Fis1 and Mff, assembles into spirals to wrap around the circumference of mitochondria, and split the membranes into two through constriction (6) Mitochondrial fusion is also facilitated by dynamin family proteins. Whereas outer membrane fusion is mediated by the Mitofusins Mfn1 and Mfn2 (FZO-1 in C. elegans), inner membrane fusion is mediated by Opa1 (EAT-3 in C. elegans).…”
Section: Introductionmentioning
confidence: 99%